Teachers’ Beliefs and Efficacy of Technological Pedagogical Content Knowledge for STEM Learning - Muthmainnah, Rifaatul; Putri, Diah Ika (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
The application of STEM in Indonesian education has grown. The TPACK framework could enhance teachers' beliefs and efficacy in STEM education. However, there need to be more details evidence of the teacher's beliefs and efficacy when facing or dealing with STEM-based learning. Therefore, exploring the teachers' views and perspectives on implementing TPACK in conducting STEM learning is crucial. This study aimed to reveal teachers' beliefs and efficacy on their TPACK in designing STEM learning. The case study method was used with 9 participants enrolled in a STEM learning program for science teachers. Teachers' self-assessment questionnaires and online interviews collected teachers' TPACK beliefs and efficacy. We analyzed quantitative data from self-assessment questionnaires using interval class analysis. We used a descriptive approach to analyze data from interviews. The results show that teachers regard themselves as highly competent in implementing their TPACK on STEM learning. Out of the three TPACK domains, teachers showed better efficacy in the integrative STEM domain. Of the three TPACK domains, teachers showed better efficacy in the integrative STEM domain than in technology-related knowledge. They are, nevertheless, generally enthusiastic about improving their technological skills. These findings reflect the urgent need to provide professional teachers programs to support this positive belief and efficacy on teachers' TPACK for STEM learning. DOI: http://dx.doi.org/10.23960/jbt.v11.i2.28402